2004
DOI: 10.1038/sj.emboj.7600455
|View full text |Cite
|
Sign up to set email alerts
|

Autophosphorylation of ataxia-telangiectasia mutated is regulated by protein phosphatase 2A

Abstract: Ionizing radiation induces autophosphorylation of the ataxia-telangiectasia mutated (ATM) protein kinase on serine 1981; however, the precise mechanisms that regulate ATM activation are not fully understood. Here, we show that the protein phosphatase inhibitor okadaic acid (OA) induces autophosphorylation of ATM on serine 1981 in unirradiated cells at concentrations that inhibit protein phosphatase 2A-like activity in vitro. OA did not induce gamma-H2AX foci, suggesting that it induces ATM autophosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
215
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(241 citation statements)
references
References 37 publications
19
215
1
2
Order By: Relevance
“…Guo et al (2002) showed that the B55a regulatory subunit dissociates from the A and C subunits after DNA damage in ATM-dependent manner. A later study also showed that ATM interacts directly with the A subunit, and that the A and C subunits coimmunoprecipitate with ATM in unirradiated human cells but dissociate after IR exposure (Goodarzi et al, 2004). They also showed that overexpression of a dominant-negative form of the C subunit-induced autophosphorylation of ATM on Ser-1981 in the absence of IR.…”
Section: Likely Candidates For Inactivators and Activators Of Atmmentioning
confidence: 92%
See 1 more Smart Citation
“…Guo et al (2002) showed that the B55a regulatory subunit dissociates from the A and C subunits after DNA damage in ATM-dependent manner. A later study also showed that ATM interacts directly with the A subunit, and that the A and C subunits coimmunoprecipitate with ATM in unirradiated human cells but dissociate after IR exposure (Goodarzi et al, 2004). They also showed that overexpression of a dominant-negative form of the C subunit-induced autophosphorylation of ATM on Ser-1981 in the absence of IR.…”
Section: Likely Candidates For Inactivators and Activators Of Atmmentioning
confidence: 92%
“…Recent articles show that two phosphatases, protein phosphatase 2A (PP2A) and protein phosphatase 5 (PP5), both affect ATM activity in vivo (Ali et al, 2004;Goodarzi et al, 2004). PP2A is a member of the protein serine/threonine phosphatase family and is composed of a catalytic (C) subunit, a scaffolding A subunit and a regulatory B subunit.…”
Section: Likely Candidates For Inactivators and Activators Of Atmmentioning
confidence: 99%
“…What is not clear yet is whether ATM pS367 and pS1893 coincide with pS1981 at the break site or whether they are associated with movement of ATM from the site to the flanking regions. Not surprisingly, protein phosphatases have also been shown to play a role in ATM activation (Ali et al, 2004;Goodarzi et al, 2004). DNA-damaged-induced acetylation of ATM has been reported by Sun et al (2005) and this was shown to run in parallel with pS1981 after radiation exposure.…”
Section: Perspectivementioning
confidence: 93%
“…In response to DSBs, a conformational change in the ATM protein stimulates it to auto-phosphorylate Ser1981 in an intermolecular manner. In contrast, the auto-phosphorylation of ATM at Ser1981 is suppressed under unperturbed conditions by a constitutive interaction with PP2A that dephosphorylates Ser1981 (Goodarzi et al 2004). Acetylation of ATM by Tip60 is also reported to be important for its full activation (Sun et al 2005).…”
Section: Pikk Kinases Are Essential For Proper Timing Of Late Origin mentioning
confidence: 99%